The Relationship Between 21st Century Learner Skills and Program Literacy Levels of Pre-Service Teachers - Kuloğlu, Ayşenur (Asya Publishing and Consultancy, 2022)
The aims to examine the relationship between preservice teachers' 21st-century learner skills and their curriculum literacy levels. 476 preservice teachers studying at the Faculty of Education of a state university in Turkey participated in the study. The relational survey model was adopted in the study. The data were collected through "21stCentury Learners Skills Use Scale" and "The Curriculum Literacy Scale". Pearson Product Moments Correlation Coefficient and regression analysis were performed. The results showed that the participants' 21st century learner skills and curriculum literacy were at a high level and their 21st century learner skills and curriculum literacy levels did not differ significantly by gender. It was found that the participant's 21st century learner skills did not significantly differ by the department. However, it was discovered that the curricular literacy levels varied greatly by department. The participants in the preschool education department were found to have higher levels of curriculum literacy levels. In addition, a significant, moderate, and positive relationship was found between the participants' 21st century learner skills and curriculum literacy. Finally, 21st-century learner skills were statistically significant predictors of program literacy levels. © 2022, Asya Publishing and Consultancy. All rights reserved.
Keywords: 21st-century learner skills; Curriculum literacy; Preservice teachers